Identification of circRNA Expression Profiles in BMSCs from Glucocorticoid-Induced Osteoporosis Model - Zhipeng Chen; Wei Lin; Shengli Zhao; Xiaoyi Mo; Zhenxing Wen; Wing Hoi Cheung; Dan Fu; Bailing Chen (Hindawi Limited, 2022)
Background. Circular RNAs (circRNAs) contribute to the regulation of many diseases. However, little is known about the role of circRNAs in the development of glucocorticoid-induced osteoporosis (GIOP). The present study is aimed at systematically characterizing the circRNA expression profiles in GIOP and predict the potential functions of the associated regulatory networks. Methods. A small animal GIOP model was developed in Sprague-Dawley rats given daily intraperitoneal doses of the synthetic glucocorticoid dexamethasone. Micro-CT and bone histomorphometry were performed to characterize the bone loss. Alizarin red S (ARS) staining and alkaline phosphatase (ALP) activity were assessed to determine the osteogenic differentiation potential of BMSCs. RNA sequencing was performed to identify differentially expressed circRNAs in BMSCs between the GIOP and normal groups, which were validated by qRT-PCR. siRNA interference experiments were used to demonstrate their function. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed to predict the functions of differentially expressed circRNAs. The microRNA (miRNA) targets of the circRNAs and circRNA-miRNA interactions were predicted. Results. Micro-CT and bone histomorphometry confirmed the rat GIOP model. Both ARS intensity and ALP activity were decreased in GIOP BMSCs. Seventeen circRNAs were identified by fold change=2.0, p<0.05, and false discovery rate<0.05, of which 7 were upregulated and 10 were downregulated. The qRT-PCR results of the selected circRNAs were consistent with the RNA-seq results and showed that circARSB and circAKT3 were significantly upregulated, while circPTEN and circTRPM7 were downregulated in the GIOP group. Further functional experiments found that downregulation of circARSB and circPTEN expression resulted in a corresponding change in osteogenic differentiation, suggesting that circARSB negatively, while circPTEN positively, regulates BMSC osteogenic differentiation. Analysis of circRNA-targeted miRNAs predicted that miR-135a-5p was associated with circARSB and circAKT3, and miR-881-3p was associated with circPTEN and circTRPM7. Furthermore, the signalling pathways associated with these differentially expressed circRNAs were predicted. Conclusions. The present study identified circARSB, circAKT3, circPTEN, and circTRPM7 as being associated with osteogenic differentiation during GIOP through a circRNA-targeted miRNA-mRNA axis, which might provide insight into the pathophysiological mechanism of GIOP.